Structural Spectrum of 2D Materials in Solution: Toward Establishing 2D Assemblies' Digital Factory. Issue 10 (25th February 2023) - Wei, Lingfei; Lin, Jinguo; Chen, Cen; Yu, Li; Lu, Canhui; Liu, Feng
Abstract: The numerous hierarchical architectures of 2D assemblies endow them with a new dimension to realize novel properties. From theoretical perspective, freedoms stem from in‐plane and out‐plane mechanical properties of 2D materials separately, which makes 2D materials embrace more than one "persistence length" giving rise to the diverse morphologies. However, the understanding of 3D architecture formation in 2D assemblies is still in its infancy. In fact, there is even no theoretical classification or reference to help clarify structural difference among numerous experimental obtained 2D assemblies. Based on the theoretical model composed by 2D sheets and Lennard‐Jones liquids, solution concentration dependence of 2D materials conformation is systematically studied, and a ln K behavior is uncovered that can realize the theoretical conformation prediction of 2D materials. More importantly, the digital production line (solution processing procedure) is set up toward establishing the 2D assemblies' digital factory. The obtained structures may provide a reference to 2D assemblies, which benefits the understanding of the structural difference among different experiments and even help to guide the experimental design of 2D assemblies with targeted architectures and properties. Abstract : Based on the theoretical model composed by 2D sheets and Lennard–Jones liquids, the correlation among the solution concentration, bending stiffness, and conformation is systematically studied in 2D materials' solution. More importantly, the digital production line (solution processing procedure) is set up toward establishing the 2D assemblies' digital factory, which predicts architectures and provides structural references as well as a foundation for classification.